HARDWOOD TRADE IN SELECTED COUNTRIES OF EASTERN EUROPE - Mračková A. (WOOD RESEARCH, 2021)
This study focuses on trade of hardwood products in selected countries of Eastern Europe, specifically the Czech Republic, Slovakia, and Hungary. It was supported by a survey conducted with companies producing products made of hardwoods. It monitors trade trends in the wood products industry, specifically focusing on lumber, wooden veneers, furniture production, musical instruments, and wooden accessories. It also addresses the current and potential import and use of the US hardwood lumber in these countries. The study is also pointing out the shortcomings of the monitored markets. The online questionnaire and follow-up phone calls were used to obtain information from companies in countries of interest. Results showed that 83.3% of Czech respondents already use imported hardwoods in their production, followed by Hungary (69.2%) and Slovakia (54.6%). Despite the relatively high values of imported hardwood products, the overall results show that there is only a small potential for an increase in import of the US hardwoods in the wood products industry in chosen countries. The utilization of tropical hardwood species will continue because of their superior properties for specialized products such as musical instruments. Results also point out the grooving importance of certified hardwoods, their utilization, and trade. © 2021 Statny Drevarsky Vyskumny Ustav. All rights reserved.